1) [tex](x^2-1)(x^2+3)=(x^2+1)^2+x[/tex]
[tex]x^4+3x^2-x^2-3=x^4+2x^2+1+x[/tex]
[tex]-3=1+x[/tex]
[tex]x = -4[/tex]
Ответ: x = -4
2) [tex](5x-2)^2-(3x-3)^2=0[/tex]
[tex]25x^2-20x+4-(9x^2-18x+9)=0[/tex]
[tex]16x^2-2x-5=0[/tex]
[tex]x1 = \frac{2+\sqrt{4+5*4*16}}{2*16} = \frac{2+18}{32} = \frac{20}{32} = 0.625[/tex]
[tex]x2 = \frac{2-\sqrt{4+5*4+16}}{2*16} = \frac{2-18}{32} = - \frac{16}{32} = -0.5[/tex]
Ответ: x1 = 0.625, x2 = -0.5
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
1) [tex](x^2-1)(x^2+3)=(x^2+1)^2+x[/tex]
[tex]x^4+3x^2-x^2-3=x^4+2x^2+1+x[/tex]
[tex]-3=1+x[/tex]
[tex]x = -4[/tex]
Ответ: x = -4
2) [tex](5x-2)^2-(3x-3)^2=0[/tex]
[tex]25x^2-20x+4-(9x^2-18x+9)=0[/tex]
[tex]16x^2-2x-5=0[/tex]
[tex]x1 = \frac{2+\sqrt{4+5*4*16}}{2*16} = \frac{2+18}{32} = \frac{20}{32} = 0.625[/tex]
[tex]x2 = \frac{2-\sqrt{4+5*4+16}}{2*16} = \frac{2-18}{32} = - \frac{16}{32} = -0.5[/tex]
Ответ: x1 = 0.625, x2 = -0.5